Akibat Hukum Pembatalan Putusan Arbitrase dalam Kaitannya dengan Prinsip Final and Binding - Andriani, Agustini (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Arbitration is an alternative effort to resolve disputes outside the court whose decisions are final and have permanent legal force that binds the parties (final and binding). However, the Arbitration and Dispute Resolution Law, namely Law Number 30 of 1999, also regulates efforts to annul the arbitration award which has legal consequences for the disputing parties. This paper is a descriptive normative legal research. The types of data used are secondary data in the form of primary legal materials and secondary legal materials. This paper discusses the legal consequences of annulment of arbitral awards which are related to the principle of Final and Binding of Arbitral Awards. This paper is descriptive in that it describes the general description of the annulment of the Arbitration Award, then describes the Final and Binding Principles in the Arbitration Award. As well as matters relating to the annulment of the arbitral award and its legal consequences. In this paper, the author concludes that the legal consequences of the annulment of the arbitration award by the District Court are that the arbitral award is considered to have never existed. In addition, with the cancellation of the arbitral award in Law Number 30 of 1999, it gives a vague meaning to the principle of final and binding which in reality the losing parties or feel that their interests are not accommodated in the arbitral award makes the decision not final and binding due to an attempt to cancel the arbitral award